The Choice of Abdominal Flap Used in Breast Reconstruction Surgery: Case Study - McVeigh, James; Kalu, Peter (Journal of the Nuffield Department of Surgical Sciences, 2020)
The incidence of breast cancer has been progressively increasing to the current level where 1 in 8 women now develop the disease. The National Breast Screening Programme has enabled us to diagnose many breast cancers at a much earlier stage. Coupled with an improved understanding of the oncoplastic approach to breast cancer surgery, genomics, hormone and targeted therapies as well as chemotherapy we now anticipate better outcomes. Despite the many advances in breast cancer there remains a significant cohort of women who are diagnosed with advanced forms of the disease that necessitates mastectomy i.e. the removal of all breast tissue. For many, reconstruction maybe immediately possible at the same time as mastectomy using either non-autologous (man-made) options such as breast implants and tissue expanders or autologous options using the latissimus-dorsi, abdominal or non-abdominal based flaps sited on thigh, buttock or lower flank tissue. Abdominal based reconstructions have evolved from crude operative procedures in which large parts of the lower anterior abdominal wall were harvested while remaining attached to the feeding vascular supply. This ‘flap’ of tissue is then rotated upon the pedicle of vessels into the new location in the breast. Pedicled Transverse Rectus Abdominus Myocutaneous (TRAM) flaps were often complicated by under-perfusion of the transferred flap resulting in fat necrosis. There were also issues with abdominal wall bulges and hernias as a result of the loss of the rectus abdominus muscle. With improvements in microsurgery the advent of free flap surgery was ushered in. Skin and fat were transplanted from the lower anterior abdominal wall using one of the rectus abdominus muscles and the perfusing artery and draining vein (donor-site). This free TRAM flap could be transplanted in the recipient-site after re-joining (re-anastomosing) the artery and vein using microsurgery. Aided by better anatomical knowledge, surgeons have been able to reduce the amount of rectus muscle sacrificed resulting in the muscle sparing-TRAM (MS-TRAM) and more latterly the deep inferior epigastric perforator (DIEP) flap which has no muscle included. The advantages of this muscle sparing approach are speedier recovery and reduced morbidity while maintaining operative cosmetic outcomes.